The impact of branding on support intentions towards supported social enterprises: The case of The Big Issue South Africa - Simons, Aaqib (School of Management Studies, 2021)
A rising problem for social enterprises within South Africa is that consumers tend to display mixed interests towards their marketing campaigns. The technological revolution has allowed consumers to become more adept and ethically sensitised at identifying deceptive marketing ploys. In light of the growing competition among many SSEs in attaining donations, managers of these organisations have realised the value in managing their organisations as brands. However, SSEs should remain aware of distinguishing their marketing from corporate brands. Past literature revealed that organisations which behave socially responsibly elicit more positive attitudes from consumers. Thus, SSEs adopting socially responsible marketing could allow them to be perceived as devoted towards their social missions, which could attract more volunteering and monetary donations. The study investigated the impact of branding on support intentions towards supported social enterprises: the case of The Big Issue South Africa. A descriptive research design was adopted. This included an online survey method that was used to acquire quantitative data from 200 participants in Cape Town, which was required to interpret conclusive findings to this investigation. The findings of the study were that consumer-brand relational authenticity (CBRA), brand trust, and customer-brand identification (CBI)] had a direct positive influence on support intentions. Attitude toward helping others (ATHO) was determined as a negative moderator between the relationship of CBI and support intentions. Alternatively, altruistic values were determined to not possess any moderating influence on the relationship between brand trust and support intentions. The findings therefore fill theoretical gaps on CBRA, brand trust and altruistic values that remained unexplored in the past. The study produced a conceptual framework explaining the branding factors that have the most significant impact in driving support intentions. This framework can be beneficial to managers of SSEs with regard to leveraging support from a local and international standpoint. However, marketers in the corporate field who are designated to attracting corporate social investment (CSI) can also draw on insights from the study in order to attract support for these CSI initiatives. The study is thus beneficial to corporate organisations as well.